The Role of Islamic Religious Education and Mosques in Community-Based Disaster Risk Reduction: IMFO and At-Thohir Mosque Los Angelos California United States - Indriya, Indriya; Najamudin, Najamudin; Falah, Saiful; Ambadar, Farhat (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2025)
Education is not only a teaching and learning process limited by four walls but also a process in which humans consciously capture, absorb, and appreciate natural events throughout the ages. IMFO was established in 1997 to coordinate the activities of the Indonesian Muslim Community in the Los Angeles area and its surroundings. The establishment of the At-Thohir Mosque began with the problems of Indonesian Muslims in the United States and in most other countries, who do not have a permanent place of worship. So, the lack of permanent places of worship is an obstacle for the young generation of Indonesian Muslims, especially in their efforts to learn and understand their place of origin. From an Islamic Religious Education perspective, this study explores the tactical steps IMFO and the At-Thohir Mosque took in addressing the current fire disaster. In this study, the researcher used the library research method, where the study used various literature, both books, notes, and reports from previous studies in collecting data, and also conducted direct interviews regarding the steps taken by IMFO and the At-Thohir Mosque in Los Angeles, United States in dealing with natural disasters such as fires. The study's results found that the mosque must also serve as a community-based disaster risk reduction centre and a place for Islamic education in the community, and the existence of the Mosque as a cultural heritage of our ancestors should continue to be preserved in community life.Keywords: Islamic Religious Education; Mosque; IMFO